2008
DOI: 10.1029/2007jd009732
|View full text |Cite
|
Sign up to set email alerts
|

Cloud processing of nitrate

Abstract: [1] The role of clouds in the transport and transformation of tropospheric pollutants was investigated through airborne measurements made out of Cleveland, Ohio, from 21 ] ratio was highest in the bulk cloud water and higher in the cloud droplet residuals compared with the below-cloud aerosols. Most of the nitrate entered the cloud water as HNO 3 , and in 30% of 43 size distributions examined, the nitrate in the cloud droplets was found in residual particle sizes smaller than those of sulfate. Simulations from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
80
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 68 publications
(92 citation statements)
references
References 77 publications
11
80
1
Order By: Relevance
“…For instance, one airborne-based study in the vicinity of Ohio indicated that NO 3 À enters cloud water predominantly through partitioning of gaseous HNO 3 , whereas SO 4 2À enters mostly through nucleation scavenging (Hayden et al, 2008 ; furthermore, they concluded that scavenging of vapors (e.g., HNO 3 ) by drops was not responsible for their results. Different conclusions in these two studies motivate an analysis of how this chemical mass concentration ratio varies inside and outside of clouds in our study region.…”
Section: Nitrate:sulfate Ratio In and Around Cloudsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, one airborne-based study in the vicinity of Ohio indicated that NO 3 À enters cloud water predominantly through partitioning of gaseous HNO 3 , whereas SO 4 2À enters mostly through nucleation scavenging (Hayden et al, 2008 ; furthermore, they concluded that scavenging of vapors (e.g., HNO 3 ) by drops was not responsible for their results. Different conclusions in these two studies motivate an analysis of how this chemical mass concentration ratio varies inside and outside of clouds in our study region.…”
Section: Nitrate:sulfate Ratio In and Around Cloudsmentioning
confidence: 99%
“…It is noted that C-ToF-AMS NO 3 À generally was below detection limits on cloud-free days in the marine boundary layer. The peak ratio in cloud water could be a result of (i) (Hayden et al, 2008); the heated air stream in the CVI inlet ranged between approximately 30e35 C.…”
Section: Nitrate:sulfate Ratio In and Around Cloudsmentioning
confidence: 99%
“…Hayden et al (2008) reported a siloxane contaminant resulting from a silicone sealant used in a counter-flow virtual impactor. Since we did not use silicone sealant in any particle accessible regions of the sampling line, we dismissed sealant as a potential contamination source.…”
Section: Report That the [Nr + 73]mentioning
confidence: 99%
“…These studies were mainly conducted at sites in North America including Wyoming (Pratt et al, 2010a), Ohio (Hayden et al, 2008), Oklahoma (Berg et al, 2009), Florida Twohy et al, 2005) and California (Coggon et al, 2014); in Europe including Schmücke (Roth et al, 2016;Schneider et al, 2017), Jungfraujoch (Kamphus et al, 2010), Åresku-tan (Drewnick et al, 2007) and Scandinavia (Targino et al, 2006); in the Arctic (Zelenyuk et al, 2010); in Central America (Cziczo et al, 2013); in western Africa (Matsuki et al, 2010); and in marine areas (Twohy and Anderson, 2008;Twohy et al, 2009;Shingler et al, 2012).…”
Section: Q Lin Et Al: a Ground-based Counterflow Virtual Impactor Cmentioning
confidence: 99%